(untitled) (Journal of School Administration Research and Development, 2022)
This article posits that high-performance implementation teams are a powerful resource for administrators when supporting the effective use of evidence-based practices (EBPs) among teachers. Yearly, administrators purchase EBPs with the expectation that positive results found in research will be reproduced in their school settings. Unfortunately, teachers’ execution of these practices can fall short of the quality needed to effect substantive progress among all students. A common response is for administrators to convene implementation teams to extend help for teachers implementing EBPs. However, many of these teams are structured traditionally and lack sufficient communication, coordination, and synergy among members to produce substantive outcomes. Yet, when administrators employ a team-directed continuous improvement process that includes a protocol for building high-performance teams, they create conditions for team members to effectively support EBP implementation, analyze performance data, cross the research-to-practice bridge, and work together to close achievement gaps.